Cycling in older adults: a scoping review - Kardan, Mohammadhossein; Akter, Taiyeba; Iqbal, Mehvish; Tcymbal, Antonina; Messing, Sven; Gelius, Peter; Abu-Omar, Karim (Frontiers in Sports and Active Living, 2023)
Introduction Regular physical activity provides many health benefits to older adults. As a well-known form of physical activity, cycling can be an appropriate means for older people to meet WHO recommendations and to improve their health. In addition, cycling can help to protect the environment and reduce greenhouse gas emissions. The primary aim of this scoping review is to identify the currently available scientific evidence and gaps of research in this field. Methods A systematic search in seven databases resulted in 7,192 studies. After the exclusion of duplicates, studies were screened by two independent reviewers in a two-stage process. Based on previously defined inclusion criteria, 123 studies were included. Data extraction was based on a descriptive analytical method, and seven categories for the main topics of studies were developed. Data were extracted by three reviewers to analyze different characteristics of included articles such as age range, study design, data type, gender, type of bicycle, and country of origin. Results The included studies covered the following topics: (1) traffic safety, (2) cycling as physical activity or for transport, (3) health benefits, (4) environmental factors, (5) facilitators and barriers, (6) application of technology and (7) promotion of cycling. Results show that the majority of studies were performed in both younger (60–79 years) and older (80+ years) adults. Most studies had an observational study design, used conventional bicycles, and were based on quantitative methods. Researchers from the United States, Netherlands, and Japan published the highest number of studies related to cycling. Discussion Traffic safety was the most prevalent focus of the included studies. Gaps were identified with regard to studies focusing on the promotion of cycling, application of technology, as well as facilitators and barriers of cycling. While research on traffic safety should continue to be a high priority for public health, potentially more research should focus on how to get older people to bicycle more. This is warranted by the proven individual and planetary health benefits of cycling and the urgency of combating climate change.